Biomimetic Hydroxylation Catalysis Through Self‐Assembly of a Bis(pyrazolyl)methane Copper–Peroxo Complex. Issue 3 (22nd December 2014) - Wilfer, Claudia; Liebhäuser, Patricia; Erdmann, Hannes; Hoffmann, Alexander; Herres‐Pawlis, Sonja
Abstract: We synthesised and characterised four copper complexes (with copper in the oxidation states I and II) with the bis(pyrazolyl)methane ligands HC(3‐ t BuPz)2 (Py) and HC(3‐ t BuPz)2 (Qu). With the quinolinyl ligand (2‐quinolinyl)bis(3‐ tert ‐butylpyrazolyl)methane [HC(3‐ t BuPz)2 (Qu)] we obtained the tetrahedral monofacial complex [CuCl{HC(3‐ t BuPz)2 (Qu)}] (C1 ) and with the pyridinyl ligand (2‐pyridinyl)bis(3‐ tert ‐butylpyrazolyl)methane [HC(3‐ t BuPz)2 (Py)] we obtained the three complexes [CuCl{HC(3‐ t BuPz)2 (Py)}] (C2 ), [CuBr2 {HC(3‐ t BuPz)2 (Py)}] (C3 ) and [CuCl2 {HC(3‐ t BuPz)2 (Py)}] (C4 ), which are also monofacially coordinated. The molecular structures were analysed and compared with density functional theory calculations, which included natural bond orbital (NBO) analysis.C1 can, when generated in situ, serve as part of a precursor, used for the activation of oxygen as tyrosinase model. We observe the self‐assembly of a peroxo–dicopper complexP with the HC(3‐ t BuPz)2 (Qu) ligand, which is able to perform catalytic hydroxylation catalysis with phenols. DFT calculations were also carried out to understand the electronic transitions responsible for the UV/Vis bands in the corresponding spectra of the peroxo species. Abstract : Herein, we present four new bis(pyrazolyl)methane–copper complexes. Furthermore, we studied the self‐assembly of a peroxo–dicopper species with catalytic hydroxylation activity of phenols by UV/Vis spectroscopy. The donor competition between pyrazolyl and pyridinyl units as well as the UV transitions of the tyrosinase model have been investigated by density functional theory.